Contribuição das neurotransmissões excitatórias nos núcleos pré-óptico mediano e paraventricular do hipotálamo na modulação da atividade nervosa simpática renal e esplâncnica - Mourão, Aline Andrade (2018)
The increase of sympathetic nervous activity (SNA) stands out as the main aggravating factor for diseases related to the cardiovascular system, as well arterial hypertension (AH). In fact, several research groups have directed their studies to the understanding of how alterations of regions and nuclei located in the central nervous system (CNS) could result in sympathetic hyperactivity and, consequently, the development and maintenance of AH. Cardiovascular control regions such as the median preoptic nucleus (MnPO) and the paraventricular nucleus (PVN) of the hypothalamus have been the focus of important investigations on the involvement of the CNS in the physiopathology of AH. However, signaling pathways that can modulate the neurons of these nuclei still need to be clarified. Therefore, the first part of this study aimed to investigate the involvement of angiotensinergic and glutamatergic neurotransmissions in the MnPO on the sympathetic activity and blood pressure increases observed in hypertensive rats. Spontaneously hypertensive rats (SHR) and rats submitted previously to the Goldblatt protocol (two kidneys; one clip; 2K1C) were used. Rats of both groups (250 to 350g, n=6) were anesthetized with urethane (1.2g/kg,i.v.) and instrumented to record mean arterial pressure (MAP), heart rate (HR) and renal sympathetic nerve activity (RSNA). Nanoinjection (100nl) of saline (NaCl, 150 mM), Losartan (AT1 receptor antagonist; 10mM) and kynurenic acid (glutamate receptor antagonist; 50mM) into the MnPO were performed. In 2K1C rats, glutamatergic blockade promoted decreases in MAP and RSNA (-19.1 ± 0.9 mmHg, -21.6 ± 2.8 %, p< 0.05) when compared to saline (-0.4 ± 0.6 mmHg, 0.2 ± 0.7 %, p < 0.05). Angiotensinergic inhibition also reduced these parameters (-11.5 ± 1.2 mmHg, -10.5 ± 1.0 %, p < 0.05) in 2K1C. In SHR, Kynurenic acid nanoinjections produced hypotension and sympathoinhibition (-21.0 ± 2.5 mmHg, -24.7 ± 2.4 %, p < 0.05), as well Losartan nanoinjections (-9.7 ± 1.2 mmHg; p < 0.05) and RSNA (-12.0 ± 2.4 %, p < 0.05). These findings support the conclusion that a tonic excitatory neurotransmission exerted by angiotensin II, and mostly by glutamate in the MnPO are involved in the elevation of blood pressure and RSNA observed in models of genetic hypertension or secondary to renal artery stenosis. In the second part of this study, we tested the hypothesis that the pro-inflammatory cytokine (PIC) tumor necrosis factor alpha (TNFα) could acutely activate the PVN neurons to promote SNA increased. For that purpose, Sprague-Dawley rats (350-550g) were anesthetized with a mixture of α-chloralose (80 mg / kg) and urethane (800 mg / kg) and instrumented for MAP, HR, splanchnic SNA (SSNA) recordings and unilateral nanoinjections in PVN. The animals were submitted to series of experiments with the following pretreatments in the PVN: vehicle (PBS, 0.5 nmol / 50 nl, n = 5), NBQX (AMPA receptor antagonist; 5.2 nmol / 50 nl n = 5) and AP5 (NMDA receptor antagonist; 24 nmol / 50 nl, n = 5). After each pretreatment, nanoinjection of TNFα (0.6 pmol / 50 nl) was performed and cardiovascular and sympathetic variables, evaluated for 60 min. TNFα nanoinjections in the PVN promoted progressive ramp-like increase of SSNA (55 ± 5.5 %) when pretreated with vehicle (3 ± 3 %, p < 0.05). However, no changes were observed in MAP (95 ± 8 mmHg vs. 94.5 ± 6.2 mmHg) and HR (400.2 bpm ± 13.5 vs. 377 ± 9 bpm) in this group. On the other hand, the blockade of ionotropic glutamate receptors AMPAR and NMDAR promoted reduction in the sympathoexcitatory response (24 ± 5% and 32 ± 6.5%, respectively) induced by the TNFα in the PVN. No changes in cardiovascular parameters were observed in these groups (NBQX: 93 ± 9 mmHg and 429 ± 10 bpm, AP5: 104 ± 3 mmHg and 439 ± 29 bpm). The following experiments sought to investigate the role of NMDA and AMPA in the maintenance of splanchnic sympathoexcitation caused by TNFα nanoinjections in the PVN. Thus, vehicle nanoinjections (PBS, 0.5 nmol / 50 nl, n = 3), NBQX (5.2 nmol / 50 nl, n = 5) and AP5 (24 nmol / 50 nl, n = 4) after 60 min of the TNFα nanoinjection in the PVN. The evaluated parameters were then recorded for additional 60 min. Post treatments did not promote significant alterations in any of the evaluated variables, suggesting that these receptors are not important in maintaining the sympathoexcitation triggered by the administration of TNFα in PVN. Finally, we evaluated whether the PVN inhibition could influence the maintenance of the sympathoexcitation induced by the TNFα. Thus, unilateral nanoinjections of the GABAA receptor agonist, muscimol (1 nmol / 50 nl, n = 5) were performed after 60 min of the TNFα nanoinjections in the PVN. Activation of GABAA receptors in PVN reversed TNFα-induced splanchnic sympathoexcitation from 173 ± 11% to 106 ± 5%, (p < 0.05). The results found in the present study indicate that the development of SSNA increase promoted by TNFα in the PVN is dependent of the ionotropic glutamate receptors AMPAR and NMDAR in this nucleus. Together these findings indicate the importance of glutamatergic neurotransmission in PVN for the generation of the sympathoexcitatory response triggered by neuroinflammation induced by (TNFα) in this nucleus. the MnPO are involved in the elevation of blood pressure and RSNA observed in models of genetic hypertension or secondary to renal artery stenosis. In the second part of this study, we tested the hypothesis that the pro-inflammatory cytokine (PIC) tumor necrosis factor alpha (TNFα) could acutely activate the PVN neurons to promote SNA increased. For that purpose, Sprague-Dawley rats (350-550g) were anesthetized with a mixture of α-chloralose (80 mg / kg) and urethane (800 mg / kg) and instrumented for MAP, HR, splanchnic SNA (SSNA) recordings and unilateral nanoinjections in PVN. The animals were submitted to series of experiments with the following pretreatments in the PVN: vehicle (PBS, 0.5 nmol / 50 nl, n = 5), NBQX (AMPA receptor antagonist; 5.2 nmol / 50 nl n = 5) and AP5 (NMDA receptor antagonist; 24 nmol / 50 nl, n = 5). After each pretreatment, nanoinjection of TNFα (0.6 pmol / 50 nl) was performed and cardiovascular and sympathetic variables, evaluated for 60 min. TNFα nanoinjections in the PVN promoted progressive ramp-like increase of SSNA (55 ± 5.5 %) when pretreated with vehicle (3 ± 3 %, p < 0.05). However, no changes were observed in MAP (95 ± 8 mmHg vs. 94.5 ± 6.2 mmHg) and HR (400.2 bpm ± 13.5 vs. 377 ± 9 bpm) in this group. On the other hand, the blockade of ionotropic glutamate receptors AMPAR and NMDAR promoted reduction in the sympathoexcitatory response (24 ± 5% and 32 ± 6.5%, respectively) induced by the TNFα in the PVN. No changes in cardiovascular parameters were observed in these groups (NBQX: 93 ± 9 mmHg and 429 ± 10 bpm, AP5: 104 ± 3 mmHg and 439 ± 29 bpm). The following experiments sought to investigate the role of NMDA and AMPA in the maintenance of splanchnic sympathoexcitation caused by TNFα nanoinjections in the PVN. Thus, vehicle nanoinjections (PBS, 0.5 nmol / 50 nl, n = 3), NBQX (5.2 nmol / 50 nl, n = 5) and AP5 (24 nmol / 50 nl, n = 4) after 60 min of the TNFα nanoinjection in the PVN. The evaluated parameters were then recorded for additional 60 min. Post treatments did not promote significant alterations in any of the evaluated variables, suggesting that these receptors are not important in maintaining the sympathoexcitation triggered by the administration of TNFα in PVN. Finally, we evaluated whether the PVN inhibition could influence the maintenance of the sympathoexcitation induced by the TNFα. Thus, unilateral nanoinjections of the GABAA receptor agonist, muscimol (1 nmol / 50 nl, n = 5) were performed after 60 min of the TNFα nanoinjections in the PVN. Activation of GABAA receptors in PVN reversed TNFα-induced splanchnic sympathoexcitation from 173 ± 11% to 106 ± 5%, (p < 0.05). The results found in the present study indicate that the development of SSNA increase promoted by TNFα in the PVN is dependent of the ionotropic glutamate receptors AMPAR and NMDAR in this nucleus. Together these findings indicate the importance of glutamatergic neurotransmission in PVN for the generation of the sympathoexcitatory response triggered by neuroinflammation induced by (TNFα) in this nucleus.